2007
DOI: 10.1007/s10895-007-0249-2
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Probe ABM for Screening Gastrointestinal Patient’s Immune State

Abstract: The fluorescent probe-aminoderivative of benzanthrone, ABM (developed at Riga Technical University, Riga, Latvia) was used to characterize the membranes of lymphocytes of cancer patients: 46 patients with gastrointestinal diseases, 13 patients having different primary localizations with massive metastases and intoxication. Patients were divided into three groups: (1) with decreased fluorescence intensity, (2) normal fluorescence intensity, (3) increased fluorescence intensity. The lymphocytes distribution amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 9 publications
1
24
1
Order By: Relevance
“…The choice to examine albumin, among the myriad of constituents in plasma, is that this protein is practically the single source of ABM binding and subsequent fluorescence in plasma (Grizunov and Dobretsov, 1994). Our earlier studies showed that within plasma, albumin is nearly alone in binding with ABM with a very high level of selectivity (Kalnina et al, 1996(Kalnina et al, , 2004(Kalnina et al, , 2007a. The distribution of ABM fluorescence (intensity) within fractions of human plasma was seen to be albumin >>> globulins >> non-specific binding by other components (i.e., 90%, ≈ 5%, < 1%, respectively).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The choice to examine albumin, among the myriad of constituents in plasma, is that this protein is practically the single source of ABM binding and subsequent fluorescence in plasma (Grizunov and Dobretsov, 1994). Our earlier studies showed that within plasma, albumin is nearly alone in binding with ABM with a very high level of selectivity (Kalnina et al, 1996(Kalnina et al, , 2004(Kalnina et al, , 2007a. The distribution of ABM fluorescence (intensity) within fractions of human plasma was seen to be albumin >>> globulins >> non-specific binding by other components (i.e., 90%, ≈ 5%, < 1%, respectively).…”
Section: Discussionmentioning
confidence: 93%
“…Investigations in this study, as in earlier studies, were performed using the fluorescent probe ABM (Kalnina and Meirovics, 1999;Kalnina et al, 2006Kalnina et al, , 2007a. This 3-aminobenzanthrone probe ( Figure 1) was synthesized by substituting a bromine atom into 3-bromobenzanthrone using an appropriate amine.…”
Section: Sample Preparation and Fluorescence Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluorescence intensity of ABM in lymphocytes suspension tended to decrease with progression of cancer. Shifts in magnitude of ABM fluorescence could reflect modifications in one/more interdependent properties of cells (Kalnina et al, 2007). As seen in the studies mentioned here, at least two parameters are responsible for this phenomenon.…”
Section: Discussionmentioning
confidence: 53%
“…The choice to examine albumin, among the myriad of constituents in plasma, is that this protein is practically the single source of ABM binding and subsequent fluorescence in plasma Dobretsov, 1994, 1998). Our earlier studies showed that within plasma, albumin is nearly alone in binding with ABM with a very high level of selectivity (Kalnina et al, 1996(Kalnina et al, , 2004(Kalnina et al, , 2007. The distribution of ABM fluorescence (intensity) within fractions of human plasma was seen to be albumin >>> globulins >> non-specific binding by other components (i.e., 90%, ≈ 5%, < 1%, respectively).…”
Section: Discussionmentioning
confidence: 93%